Study on Smart Home Interface Design Characteristics Considering the Influence of Age Difference: Focusing on Sliders - Yu, Na; Ouyang, Ziwei; Wang, Hehe (Frontiers in Psychology, 2022)
Sliders are one of the most common components used in the smart home user interface. Since aging adaptable design of smart home interface has become an inevitable trend in the global aging situation, this paper focused on the sliding component design of smart home interface, examined the effects of button design characteristics (button size, track color and sliding orientation) on user performance of different age groups, in order to obtain the design standard of sliding component for the elderly. Our results revealed the user performance was better in the horizontal sliding orientation with 5mm and larger size button for both the young and the middle-aged and elderly people, while the results of the track color was different. For the older group, slider with color gradient track led to better user performance, while the track color only had little effect on the performance of the younger group.